2014
DOI: 10.1128/iai.01293-13
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Glycan Lacto-N-Fucopentaose III Requires Clathrin-Mediated Endocytosis To Induce Alternative Activation of Antigen-Presenting Cells

Abstract: The mechanism of alternative activation of antigen-presenting cells (APCs) is largely unknown. Lacto-N-fucopentaose III (LNFPIII) is a biologically conserved pentasaccharide that contains the Lewis x trisaccharide. LNFPIII conjugates and schistosome egg antigens, which contain the Lewis x trisaccharide, drive alternative activation of APCs and induce anti-inflammatory responses in vivo, preventing inflammation-based diseases, including psoriasis, transplant organ rejection, and metabolic disease. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…Since B cells show a very restricted expression of those receptors [ 41 ], we hypothesized that other C-type lectin receptor-expressing cell types in the splenic marginal zone, such as macrophages or dendritic cells, bind SEA and provide additional signals to the marginal zone B cells to support Breg cell development. Among the accessory cell types, macrophages of the splenic marginal zone were of particular interest because of their known interactions with marginal zone B cells [ 28 , 42 ] and schistosome antigens [ 43 , 44 ]. However, it was unknown whether marginal zone macrophages can capture SEA in vivo and are important for B cell IL-10 expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since B cells show a very restricted expression of those receptors [ 41 ], we hypothesized that other C-type lectin receptor-expressing cell types in the splenic marginal zone, such as macrophages or dendritic cells, bind SEA and provide additional signals to the marginal zone B cells to support Breg cell development. Among the accessory cell types, macrophages of the splenic marginal zone were of particular interest because of their known interactions with marginal zone B cells [ 28 , 42 ] and schistosome antigens [ 43 , 44 ]. However, it was unknown whether marginal zone macrophages can capture SEA in vivo and are important for B cell IL-10 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages of the splenic MZ were of particular interest because of their known interactions with MZ B cells during steady state [ 28 , 42 ] and their expression of SIGN-R1. This C-type lectin receptor was found to bind schistosome antigens in vitro by using SIGN-R1-overexpressing fibroblasts [ 43 , 44 ]. However, it was unknown whether MZ macrophages can capture SEA in vivo and are important for B cell IL-10 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although the expression of other myeloid CLRs, such as Langerin and DC‐SIGN, is elevated in DCs and keratinocytes in psoriatic skin, the functional roles of these CLRs still remain obscure . Elevated expression of these molecules may reflect accumulation and/or activation of Langerhans cells and DCs and altered differentiation of keratinocytes.…”
Section: Myeloid Clrs In Cutaneous Immunitymentioning
confidence: 99%
“…Several recent reports showed that LNFPIII from soluble egg antigen also modulate immune response [49]. The protective role of LNFPIII for host is to alleviate hepatosteatosis and insulin resistance [50].…”
Section: Parasite – Host Communicationmentioning
confidence: 99%